Estudo Químico de Hippeastrum puniceum (Lam.) Kuntze: uma espécie da família Amaryllidaceae - Feu, Amanda Eiriz (2020)
The Amaryllidaceae family is known primarily for producing biologically active alkaloids, isoquinolines, which exhibit an extensive variety of biological activity as antitumor, antifungal, antiviral, antiparasitic, antimalarial and, no less importantly, t